2015
DOI: 10.1037/rep0000056
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of life satisfaction after traumatic brain injury: Influence of life roles, age, cognitive disability, and depressive symptoms.

Abstract: Objectives 1) Identify life satisfaction trajectories after moderate to severe traumatic brain injury (TBI), 2) establish a predictive model for these trajectories across the first 5 years post-injury, and 3) describe differences in these life satisfaction trajectory groups, focusing on age, depressive symptoms, disability, and participation in specific life roles,. Research Method Analysis of the longitudinal TBI Model Systems National Database was performed on data collected prospectively at 1, 2, and 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 69 publications
4
67
0
Order By: Relevance
“…Our experiment used a mouse model in which TBI was induced with the weight-drop method, which frequently resulted in cortical contusion and a series of neurological impairments. 39 In our previous studies, Cb treatment was shown to potentially attenuate cognitive disorder in mice. [40][41][42] Consistent with our present study, Cb treatment significantly ameliorated TBI-induced neurological deficits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our experiment used a mouse model in which TBI was induced with the weight-drop method, which frequently resulted in cortical contusion and a series of neurological impairments. 39 In our previous studies, Cb treatment was shown to potentially attenuate cognitive disorder in mice. [40][41][42] Consistent with our present study, Cb treatment significantly ameliorated TBI-induced neurological deficits.…”
Section: Discussionmentioning
confidence: 95%
“…Neurological deficits are often the cause of disability after TBI. Our experiment used a mouse model in which TBI was induced with the weight‐drop method, which frequently resulted in cortical contusion and a series of neurological impairments . In our previous studies, Cb treatment was shown to potentially attenuate cognitive disorder in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Other predictors of PTD are discussed in the “Predictors/etiology of depression” section. Finally, PTD up to and beyond 10 years post-injury was associated with lower and declining life satisfaction4042 and with poorer quality of life after TBI 3,25,4345. A study by Diaz et al45 reported that those with depression after TBI had greater impairments in all domains of the Short Form Health Survey (SF-36), a health-related quality of life measure, compared to those without depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that life roles, such as being a driver, are important for life satisfaction after injuries, such as TBI and SCI (Juengst et al, 2015). Future studies need to examine participation in life roles; moreover, the personal importance and changes in these specific life roles (for example, driving and community mobility) after trauma injuries.…”
Section: Introductionmentioning
confidence: 99%